Identification of antibody specificity using adsorption-elution studies with incompatible packed red cell unit - Kella Nivedita; Somnath Mukherjee; Debasish Mishra; Namrata Datta; Ansuman Sahu; Satya Prakash (Asian Journal of Transfusion Science)
Antibody identification is usually performed by antibody identification panels which are specially selected red cells, at least one of which has a homozygous expression for all clinically significant blood group antigens facilitating agglutination upon reaction with specific antibodies even exhibiting dosage. In general, adsorption elution is used in determining antibody specificities in the background of multiple alloantibodies with or without autoantibodies. Herein, we present a classic case where a routine antibody identification panel failed to detect a solo antibody from patient serum, following which we tested the eluate obtained after adsorption with a cross-match incompatible packed red blood cell unit using the same antibody identification panel, which unveiled the Fyb antibody.